IMPACT OF AERATION ON OIL PALM EMPTY FRUIT BUNCHES DECOMPOSITION (Jurnal Teknologi Industri Pertanian, 2023)
Oil Palm Empty Fruit Bunches (OPEFB) is one of the large solid wastes produced in oil palm industries. In this study, a technique of fast composting of oil palm EFB was carried out. This research aims to assess the effect of aeration on water content, the dynamics of temperature, fungal growth, and the carbon-nitrogen ratio of the EFB. Treatments tested in this study were three types of ligninolytic fungal isolates as decomposers (Omphalina sp, Pholyota sp, and Omphalina sp + Pholyota sp.) and two types of aeration, i.e., with or without aeration in the composting pile. The study was done for seven weeks on open land. The water content of composting piles on aeration treatments (48.7-53.7%) was slightly higher than treatments without aeration (37.2-45.56%). Based on the parameters of increasing temperature, the EFB decomposition process increased and reached a maximum in the second week and then decreased in the period incubation of 7 weeks. Giving aeration to the EFB pile inoculated with decomposer seems to produce slightly better mycelium growth by about 20% than those without aeration. In general, the values of the C/N ratio were lower in the aerated EFB piles compared to those without aeration. Management of aeration, such as controlling the period of aeration, is needed to maintain EFB moisture in the presence of aeration or add material that keeps the aeration will maintain the optimum water content in a pile.Keywords: decomposers, ligninolytic, Omphalina sp., Pholyota sp